Preliminary Validation of the Severity of Nail Psoriasis Score (SNAPS) for the Assessment of Nail Psoriasis in Patients With Psoriatic Arthritis. Issue 3 (July 2021) - Antony, Anna; Saeed, Sadaf; Hart, Darren; Nair, Preeti; Cavill, Charlotte; Korendowych, Eleanor; McHugh, Neil; Lovell, Christopher; Tillett, William
Background: Psoriatic nail dystrophy is infrequently assessed in routine care and observational cohorts due to the lack of a feasible validated outcome measure. Objective: To assess the measurement properties of the "Severity of NAil Psoriasis Score" (SNAPS) in PsA. Methods: Nail photography was performed on prospectively recruited patients at baseline and 6 months. The modified Nail Psoriasis Severity Index (mNAPSI) and Physician Nail Visual Acuity Scale (PhNVAS) were comparator instruments for construct validity. Reliability and feasibility were assessed using intra-class correlations (ICCs) and timed scoring. Responsiveness was assessed by correlating the changes in SNAPS, mNAPSI and PhNVAS. Retrospective data from the Bath PsA database was further utilized to assess responsiveness. Results: 21 patients participated in the prospective validation at baseline. Inter- and intra-rater reliability of SNAPS were 0.94 and 0.93-0.96 (p ≤ 0.005). Mean times required to score SNAPS and mNAPSI were 59 and 136 seconds. There were strong correlations between SNAPS and mNAPSI (r = 0.95, p < 0.001) and PhNVAS (r = 0.77, p < 0.001) at baseline. There was a significant reduction in the mNAPSI and SNAPS (p < 0.005) at 6 months and a strong correlation between the change in SNAPS and mNAPSI (rho = 0.838, p < 0.001). Historical data from 57 patients commenced on Etanercept were evaluated. Mean SNAPS reduced from 3.6 to 2.0 at 3 months and 1.2 at 6 months (p < 0.05). Change in SNAPS correlated with changes in Psoriasis Area Severity Index and Dermatology Quality of Life at 3 and 6 months (r≥0.510; p ≤ 0.003). Conclusion: SNAPS is a feasible, reliable and responsive outcome instrument for psoriatic nail dystrophy.